2006
DOI: 10.1086/504322
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality Associated with an Outbreak of Hepatitis E among Displaced Persons in Darfur, Sudan

Abstract: This large epidemic of HEV infection illustrates the dramatic impact of this disease on pregnant women. Timely interventions and a vaccine are urgently needed to prevent mortality in this special group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
156
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 23 publications
2
156
4
1
Order By: Relevance
“…The reason for the lower replication rate of gt1 and gt3 in placenta‐derived JAR cells compared to JEG‐3 and BeWo cells is currently unclear; however, this could be due to a differential host factor expression required for efficient HEV replication. The first HEV outbreak with reported cases of symptomatic pregnant women was documented in 1987 in Nepal,38 and most of the recent gt1 outbreaks were detected in refugee camps in developing countries, including Somalia,39 Kenya,40 Sudan,41 and Uganda 9. There are, in addition, reports mainly from Egypt in which gt1 infections during pregnancy were not associated with morbidity 42, 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the lower replication rate of gt1 and gt3 in placenta‐derived JAR cells compared to JEG‐3 and BeWo cells is currently unclear; however, this could be due to a differential host factor expression required for efficient HEV replication. The first HEV outbreak with reported cases of symptomatic pregnant women was documented in 1987 in Nepal,38 and most of the recent gt1 outbreaks were detected in refugee camps in developing countries, including Somalia,39 Kenya,40 Sudan,41 and Uganda 9. There are, in addition, reports mainly from Egypt in which gt1 infections during pregnancy were not associated with morbidity 42, 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…emerging virus | zoonosis H epatitis E virus (HEV) gained notoriety as the cause of epidemics and sporadic cases of acute hepatitis in developing countries; examples include the 29,300 cases that occurred during the New Delhi outbreak in 1956 and the 2,621 cases reported over 6 mo in an Internally Displaced Persons Camp in Darfur in which pregnant women, as has been reported previously (1), had the highest mortality rate (26-31%) (2). HEV is the most or secondmost important cause of acute hepatitis in adults in developing countries.…”
mentioning
confidence: 99%
“…7,24,25,43,45 Tables 3 and 4 7,11,12,[42][43][44][45][46][48][49][50] highlight the sporadic and epidemic studies of HEV induced AVH/ALF reported in pregnant females.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
“…52 Further, certain studies have also documented that However, the above mentioned facts have emanated predominantly from the Indian subcontinent Northern India and Pakistan, Somalia, Sudan and Nepal. 7,11,12,50 The information of HEV and its relation to pregnancy in southern India needs appropriate prospective evaluation.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
See 1 more Smart Citation